Electron emission in ionization of He and Ne by fast dressed oxygen ions and projectile-charge-state dependence - Biswas, Shubhadeep (2015)
The double-differential cross sections (DDCS) of low-energy electrons emitted at forward, backward, and perpendicular directions are reported for collisions of 3.75 MeV/u Oq+ (q=5, 6, 7, 8) projectiles with He and Ne targets. The measured DDCS are found to be deviating from the q2 dependence throughout the entire energy region. The effect of projectile electrons, for the dressed ions, as a function of the impact parameter is clearly noticeable for large as well as low-impact parameter collisions. We also present a theoretical calculation based on the prior form of the continuum distorted wave-eikonal initial state approximation, in which the projectile-active electron interaction is modeled with the Green-Sellin-Zachor potential. This particular representation of the potential has been proven to give good qualitative results for projectiles with residual electrons. In addition to the total DDCS, the individual contributions from target ionization, projectile electron loss, and simultaneous ionization processes are also calculated. The total DDCS obtained from these calculations are shown to be in excellent agreement with the experimental observations.